„Hauzeracy idą!”. Piosenka na łódzkim podwórku - Woźniak, Krzysztof Paweł (Zeszyty Wiejskie, 2016)
The article discusses folk music in Lodz developed in labour community and the changes it underwent from its birth in the 70’s of the 19th century. The unique characteristics of this music phenomenon were the street bands playing in the yards of tenement houses. They were strictly attributable to the Polish workers and not present among German and Jewish community. The repertoire included folk rural songs whose lyrics were often changed to meet the urban reality, and the popular radio songs, especially in the interwar period. After the World War II due to political changes and easy access to recorded music, backyard music bands stopped performing. The revival took place in the 20th century due to the arising interest in working class culture. The conditions and places where bands performed changed. The majority of them were sponsored by the state and presented reconstructed folk music. Some of them exist nowadays as relicts of old labour tradition.